2021
DOI: 10.1155/2021/6655198
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Eco‐Friendly Sandwich Wall with Rice Husk Recycled Concrete

Abstract: In the construction industry, an approach to alleviate the environmental problem is to apply ecological composite materials to the construction field. In this paper, the authors added the recycled aggregate and the rice husks to the concrete and measured the strengths of rich husk recycled concrete (RHRC) with different factors as well as determined the constitutive model. Subsequently, the flexural experiment of RHRC sandwich wall was carried out and analyzed in detail, which proved that it could bear the win… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Considering the solidification effect of cement on heavy metals and low cost of fly ash and bottom ash, the application in cement-stabilized macadam base has broad application prospects and is beneficial to reduce construction cost and promote the process of waste incineration, especially in developing countries. D. S. Chen et al [29] investigated the mechanical properties of rice husk recycled concrete (RHRC) and employed flexural test on the RHRC sandwich wall. e results showed that the compressive strength of RHRC was reduced with rising rice husk content.…”
mentioning
confidence: 99%
“…Considering the solidification effect of cement on heavy metals and low cost of fly ash and bottom ash, the application in cement-stabilized macadam base has broad application prospects and is beneficial to reduce construction cost and promote the process of waste incineration, especially in developing countries. D. S. Chen et al [29] investigated the mechanical properties of rice husk recycled concrete (RHRC) and employed flexural test on the RHRC sandwich wall. e results showed that the compressive strength of RHRC was reduced with rising rice husk content.…”
mentioning
confidence: 99%